Vaginal Treatment of Vaginal Cuff Dehiscence with Visceral Loop Prolapse: A New Challenge in Reparative Vaginal Surgery? - Salvatore Andrea Mastrolia; Edoardo Di Naro; Luca Maria Schonauer; Maria Teresa Loverro; Beatrice Indellicati; Mario Barnaba; Giuseppe Loverro (Case Reports in Obstetrics and Gynecology)
Vaginal cuff dehiscence is a rare, but potentially morbid, complication of total hysterectomy and refers to separation of the vaginal cuff closure. The term vaginal cuff dehiscence is frequently interchanged with the terms of cuff separation or cuff rupture. All denote the separation of a vaginal incision that was previously closed at time of total hysterectomy. After dehiscence of the vaginal cuff, abdominal or pelvic contents may prolapse through the vaginal opening. Bowel evisceration, outside the vulvar introitus, can lead to serious sequelae, including peritonitis, bowel injury and necrosis, or sepsis. Therefore, although prompt surgical and medical intervention is required to replace prolapsed structures, the main problem remains the reconstruction of vaginal vault. In case of recent hysterectomy, vaginal reparation only requires the approximation of vaginal walls, including their fascia, while if dehiscence occurs after a long time from hysterectomy, the adequate suspension of the vaginal vault has to be taken into consideration. In this report we describe the case of a postmenopausal patient, undergoing surgical emergency because of the evisceration of an intestinal loop through a dehiscence of vaginal vault, after numerous reconstructive vaginal surgeries for vaginal prolapse. This paper analyzes clinical circumstances, risk factors, comorbidity, and clinical and surgical management of this complication.